Pengaruh Overconfidence Managerial Terhadap Keputusan Lending dan Kinerja Bank Pembangunan Daerah Di Indonesia - Neny Nopita Dewi; Fitri Santi; Trisna Murni (Student Journal of Business and Management, 2021)
The purpose of this study to discuss bias overconfidence behavior among top managers and examine its impact to lending decisions and performance Regional Development Banks (BPD) in Indonesia. The research method uses quantitative methods with descriptive and verification research approaches by looking at the effect of managerial overconfidence on lending decisions and performance BPD in Indonesia in the last 10 years (2009-2018). The results show that managerial overconfidence has no significant effect on lending decisions (NPL-to-loan and loan change) and performance (ROA and ROE) of BPD in Indonesia. However, managerial overconfidence has a positive effect on NPL-to-Equity The effects of lending nploan and loanchange decisions have no positive effect on the performance (ROA and ROE) of BPD in Indonesia.